Current situation, bottlenecks, and path options for the development of capital flows and integration in the Yangtze River Delta region - Yang, Jing; Li, Guofan; Zhong, Zhuowen; Li, Qiang; Du, Guolei; Guo, Jinhan (Frontiers in Sustainable Cities, 2023)
Introduction Capital plays a crucial role in the development of regional economies, especially in low-income regions where it acts as a primary driver of economic growth. Efficient capital flow is essential for optimizing resource allocation and facilitating the development of integrated capital markets. This passage introduces the topic of capital, capital flow, and capital market integration and highlights their significance in regional development. Methods To gain a comprehensive understanding of capital flow and integration in the Yangtze River Delta region, the researchers conducted a connotative analysis. They constructed indicators from various aspects, including social fixed asset investment, bank capital flow, government transfer payments, social financing structure, and foreign direct investment. By utilizing these indicators, the researchers aimed to assess the current situation and identify bottlenecks related to capital flow and integration. Additionally, they drew on experiences from foreign capital flow and integration development to enrich their analysis. Results The analysis revealed several primary bottlenecks affecting capital flow and integration in the Yangtze River Delta region. These bottlenecks include an unsound banking management system, the presence of government competition and administrative barriers, and shortcomings within listed companies. The results highlight the specific challenges that hinder the smooth functioning and integration of capital in the region. Discussion To promote the development of capital flows and integration in the Yangtze River Delta region, the researchers propose various recommendations. These suggestions include promoting the development of listed companies, establishing a robust banking management model, improving relevant government policies, and optimizing the investment environment. These recommendations serve as important guidelines for policymakers to enhance capital flow and integration in the Yangtze River Delta city cluster. Furthermore, they emphasize the need to strengthen financial supervision and improve institutional mechanisms within the three provinces and one city comprising the region.